English-Spanish, Spanish-English electrical and computer engineering dictionary = Diccionario de ingenieria electrica y de computadoras ingles/espanol, espanol/ingles - Kaplan, Steven M.
The English-Spanish, Spanish-English Electrical and Computer Engineering Dictionary offers comprehensive up-to-date coverage of virtually every word and phrase you are likely to encounter in the electrical and computer engineering literature. The only book of its kind, it contains more than 95,000 entries - nearly 50,000 in each language. Designed for quick reference and clarity, it features an extremely user-friendly format that directs you instantly to the precise. Equivalent you need without first rerouting you through a maze of irrelevant terms and phrases. For idiomatic expressions, conceptual equivalents are provided, rather than literal translations. And phrases that begin with the same word or words are provided as separate entries.